2017
DOI: 10.1177/1753193417740850
|View full text |Cite
|
Sign up to set email alerts
|

Lunate fractures and associated radiocarpal and midcarpal instabilities: a systematic review

Abstract: The aim of this study was to analyse lunate fractures and any associated osseo-ligamentous injuries. A systematic review identified 34 cases. We identified carpal instabilities at the radiocarpal and midcarpal joints in volar and dorsal directions. Radiocarpal instabilities (10/34) were usually dorsoradial (8/10), with a transverse lunate fracture, best seen on a coronal image. Midcarpal instabilities (24/34) were usually volar (14/18), with a volar lunate shear fracture, best seen on a sagittal image. Instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…(2019) stated, in their CBCT study of patients with wrist pain and normal radiographs, that the trapezium is the most common radiographically occult radiocarpal fracture. Lunate fractures are described in the literature as rare, comprising 0.5–1% of all carpal fractures and when they are found, they are usually part of a more complex fracture pattern with concomitant fractures, of other carpal bones or the distal radius, and ligament injuries leading to midcarpal instability ( Shunmugam et al., 2018 ). Our study adds information on the existence of isolated lunate fractures, which comprised 8% of the carpal fractures found during the CBCT period.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) stated, in their CBCT study of patients with wrist pain and normal radiographs, that the trapezium is the most common radiographically occult radiocarpal fracture. Lunate fractures are described in the literature as rare, comprising 0.5–1% of all carpal fractures and when they are found, they are usually part of a more complex fracture pattern with concomitant fractures, of other carpal bones or the distal radius, and ligament injuries leading to midcarpal instability ( Shunmugam et al., 2018 ). Our study adds information on the existence of isolated lunate fractures, which comprised 8% of the carpal fractures found during the CBCT period.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture typically occurs together with other carpal fractures, perilunate dislocations, or ligament disruptions. Closed treatment with prolonged cast immobilization for 6 weeks for undisplaced lunate fractures is the recommended form of treatment [5]. Early surgical intervention with K wire or screws after good anatomical reduction reduces the risk of developing osteonecrosis in displaced lunate fractures [5].…”
Section: Discussionmentioning
confidence: 99%
“…He found that volar dislocation at the midcarpal joint (14 out of 34 cases) is more common than dorsal dislocation (4 out of 34 cases). 8 In the traditional perilunate injury without a lunate fracture, dislocation in a dorsal direction is the most common. 9 In our three cases, all of the lunate fractures demonstrated a similar pattern, which resembled the Theissen type-I fracture pattern, that is, a coronal fracture at the volar lip.…”
Section: Discussionmentioning
confidence: 99%